2009
DOI: 10.4167/jbv.2009.39.4.363
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Acute Gastroenteritis in Seoul, Korea, During May 2004 and June 2007

Abstract: Acute gastroenteritis (AGE), which is one of the most common diseases worldwide, primarily occurs in infants and young children in both developed and developing countries. To investigate the prevalence of AGE in Korea, 6,788 stool specimens collected from hospitalized patients with AGE in Seoul, Korea from March 2004 to June 2007 were analyzed by enzyme immunoassay, reverse transcription-PCR, DNA sequencing and phylogenetic analysis. Enteric viruses and bacteria were detected in 2,955 (43.5%) and 1,389 (20.5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
2
11
0
2
Order By: Relevance
“…An acute portant causative viral agents [3]. In our study, the overall prevalence of viral gastroenteritis was 44.8%, a finding that agrees with previous studies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…An acute portant causative viral agents [3]. In our study, the overall prevalence of viral gastroenteritis was 44.8%, a finding that agrees with previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…More cases are needed to evaluate the significance of these symptoms. Similar to what was found in previous studies, diarrhea was significantly associated with rotavirus (93.7%), adenovirus (88.9%), and norovirus (65.6%) (P<0.05) [1,3].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, viral gastroenteritis generally showed a double peak of incidence during spring and autumn. The peak incidence of rotavirus had been generally known as in winter 43,44) ; however, a delay in peak incidence of rotavirus has been reported in some studies [45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may relate to the fact that the VP6-specific IgG levels produced by the Koreans participating in this study are higher than those generated by the Indians and Brazilians (11, 12). The surveillance of acute gastroenteritis in Seoul, Korea showed rotavirus is the most common pathogen in infants with viral gastroenteritis (42.7%, 496/1,161) (13). In a study of rotavirus surveillance testing on all the newborns who were admitted to the nursery in Korea, 47 of 61 neonates had no symptoms of gastroenteritis such as fever, vomiting and diarrhea (14).…”
Section: Discussionmentioning
confidence: 99%